Carrier Multiplication and Photoexcited Many-Body States in Solution-Processed 2H-MoSe2 - Coleman, Jonathan; Carey, Tian (My University, 2025)
Carrier multiplication (CM), where a single high-energy photon generates multiple electron−hole pairs, offers a promising route to enhance the efficiency of solar cells and photodetectors.Transition metal dichalcogenides, such as 2H- MoTe2 and 2H-WSe2, exhibit efficient CM. Given the similar electronic band structure of 2H-MoSe2, it is expected to show comparable CM efficiency. In this study, we establish the occurrence and efficiency of CM in a solution-processed thin film of bulk-like 2H-MoSe2. We characterize the dynamics of excitons and free charge carriers by using ultrafast transient optical absorption and terahertz spectroscopy. At higher photon energy the efficiency is comparable to literature results for 2H- MoTe2 grown by chemical vapor deposition (CVD) or in bulk crystalline form. At higher photon energies the experimental CM efficiency is reproduced by theoretical modeling. We also observe CM for photon energies below the energetic threshold of twice the band gap, which is most probably due to subgap defect states. Transient optical absorption spectra of 2H-MoSe2 exhibit features of trions from which we infer that photoexcitation leads to free charge carriers. We find no signatures of excitons at the indirect band gap. From analysis of the frequency dependence of the terahertz conductivity we infer that scattering of charge carriers in our sample is less than for CVD grown or bulk crystalline 2H-MoTe2. Our findings make solution-processed 2H-MoSe2 an interesting material for exploitation of CM in photovoltaic devices.
PUBLISHED
Cited by: 0; All Open Access, Hybrid Gold Open Access
Keywords: carrier multiplication; excitons; trions; solution-processed transition metal dichalcogenide; transient absorption spectroscopy; terahertz spectroscopy